The features of the initial vegetative tone in patients with vertigo - Федорченко, Світлана Валеріївна (ScienceRise: Medical Science, 2016)
Vegetative dysfunction is most often manifested as vertigo. The presence of vestibular dysfunction on the background of vegetovascular dystonia is conditioned by the close functional connection between vestibular and vegetative nervous system. The study of interaction and mutual connection between vertigo and vegetative functioning is necessary to improve the effectiveness of diagnostic and treating-rehabilitative arrangements. Methods. 159 patients with vertigo were examined according to the scheme for revelation of the signs of vegetative disorders. All patients were divided in four groups, taking into account the cause of vertigo. The first group included 47 patients with acute ischemia of brain in vertebrobrasilar basin. The second one included 30 patients with craniovertebral pathology and vascular anomalies of the neck part. The third one – 40 patients with the injury of peripheral vestibular analyze, the fourth group – 42 patients with psychogenic vertigo. Results. The analysis of parameters of VNS functioning in examined patients testified to the intrasystemic dysregulation; decrease of reserve possibilities of VNS adaptation, manifestations of the disorders of cerebral homeostasis and disturbance of the correct functioning of non-specific cerebral systems. Conclusions. The interconnection between vertigo and central mechanisms of vegetative regulation that must be considered as the components of rehabilitative potential was revealed. These regularities can be the base for using integration approach in the choice of rehabilitative interventions at vertigo in patients with neurological pathology